In Single-Level, Open, Posterior Lumbar Fusion, Does Transforaminal Lumbar Interbody Fusion or Posterolateral Fusion Lead to Better Outcomes?. Issue 1 (1st January 2023) - Chanbour, Hani; Steinle, Anthony M.; Tang, Alan R.; Gardocki, Raymond J.; Abtahi, Amir M.; Stephens, Byron F.; Zuckerman, Scott L.
Abstract : Abstract : BACKGROUND: Two common approaches for open, one-level, posterior lumbar fusions include transforaminal lumbar interbody fusion (TLIF) and posterolateral fusion (PLF) alone without an interbody. OBJECTIVE: To compare TLIF vs PLF alone in (1) discharge disposition, (2) return to work (RTW), and (3) patient-reported outcomes (PROs). METHODS: A single-center, retrospective cohort study was undertaken between October 2010 and May 2021, all with a 1-year follow-up and excluding patients with isthmic spondylolisthesis. Minimum clinically important difference for each PRO was used, which included Numeric Rating Scale (NRS) and Oswestry Disability Index (ODI). Logistic/linear regression controlled for age, body mass index, disc height, flexion-extension movement, amount of movement on flexion-extension, and spondylolisthesis grade. RESULTS: Of 850 patients undergoing open, 1-level, posterior lumbar fusion, 591 (69.5%) underwent a TLIF and 259 (30.5%) underwent a PLF alone. Patients undergoing TLIF were younger (59.0 ± 11.3 vs 63.3 ± 12.6, P < .001), had higher body mass index (31.3 ± 6.6 vs 30.2 ± 12.6, P = .019), and more often had private insurance (50.3% vs 39.0%, P < .001). Regarding discharge disposition, no significance was found in multivariate regression (odds ratio = 2.07, 95% CI = 0.39-10.82, P = .385) with similar RTW between TLIF and PLF alone (80.8% vs 80.4%, P = .645) (odds ratio = 1.15, 95% CI = 0.19-6.81, P = .873). Regarding PROs, patients undergoing a TLIF had higher preoperative (6.7 ± 2.3 vs 6.4 ± 2.5, P = .046) and 3-month NRS-back pain (3.4 ± 2.6 vs 2.9 ± 2.5, P = .036), with similar 12-month NRS-back pain. Regarding NRS-leg pain, no differences were observed preoperatively ( P = .532) and at 3 months ( P = .808). No other significant differences were observed in ODI. CONCLUSION: TLIF patients had slightly higher NRS-back pain at baseline and 3 months, but similar NRS-leg pain, despite the added risk of placing an interbody. No differences were seen in discharge disposition, RTW, and 12-month pain scores and ODI.